Radial Head and Neck Ostectomy Maintained Elbow Joint Function in a Labrador Retriever with Type 1 Congenital Elbow Luxation - Pankowski, Anne; McCarthy, Jessica (VCOT Open, 2024)
A 6-month-old Labrador Retriever was diagnosed with a Type 1 caudolateral congenital right elbow luxation. A radial head and neck ostectomy was performed with no surgical attempt to further stabilize the elbow joint. One year after surgery, objective gait analysis showed only a mild asymmetry in peak vertical forces. Pre- and postoperative Liverpool Osteoarthritis in Dogs scores showed a decrease in perceived pain and a reduction in signs of osteoarthritis. In dogs with congenital radial head luxation, a radial head and neck ostectomy without surgical joint stabilization may be a viable, simple option for a one-time intervention that can reduce pain and signs of secondary osteoarthritis and improve limb function.
Keywords: radial head and neck ostectomy; canine elbow luxation; radial luxation; radial ostectomy